2019
DOI: 10.1096/fj.201801483rr
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial adaptation in human mesenchymal stem cells following ionizing radiation

Abstract: Mitochondria are highly dynamic organelles that respond rapidly to a number of stressors to regulate energy transduction, cell death signaling, and reactive oxygen species generation. We hypothesized that mitochondrial remodeling, comprising both structural and functional alterations, following ionizing radiation (IR) may underlie some of the tenets of radiobiology. Mesenchymal stem cells (MSCs) are precursors of bone marrow stroma and are altered in acute myeloid leukemia and by radiation and chemotherapy. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 72 publications
(127 reference statements)
0
6
0
Order By: Relevance
“…Limited studies have indicated the potential impacts of physical stimuli or exogenous toxins on the mitochondrial dynamics of MSCs. Patten et al (2019) observed that mitochondrial length in human BMSCs was slightly increased 4 h after exposure to 2 Gy radiation. They further demonstrated that Opa1 knockdown in mouse embryonic fibroblasts induced a decline in their adaptation to radiation, suggesting that mitochondrial networks may also be involved in the regulation of BMSC adaptation to radiation (Patten et al, 2019).…”
Section: Mitochondrial Dynamics In Mscs Under Physical Stress and Toxinsmentioning
confidence: 97%
See 1 more Smart Citation
“…Limited studies have indicated the potential impacts of physical stimuli or exogenous toxins on the mitochondrial dynamics of MSCs. Patten et al (2019) observed that mitochondrial length in human BMSCs was slightly increased 4 h after exposure to 2 Gy radiation. They further demonstrated that Opa1 knockdown in mouse embryonic fibroblasts induced a decline in their adaptation to radiation, suggesting that mitochondrial networks may also be involved in the regulation of BMSC adaptation to radiation (Patten et al, 2019).…”
Section: Mitochondrial Dynamics In Mscs Under Physical Stress and Toxinsmentioning
confidence: 97%
“…Patten et al (2019) observed that mitochondrial length in human BMSCs was slightly increased 4 h after exposure to 2 Gy radiation. They further demonstrated that Opa1 knockdown in mouse embryonic fibroblasts induced a decline in their adaptation to radiation, suggesting that mitochondrial networks may also be involved in the regulation of BMSC adaptation to radiation (Patten et al, 2019). Yin et al (2017) revealed that low-level laser exposure facilitated mitochondrial biogenesis via upregulation of molecules associated with both mitochondrial fusion (Mfn1, Mfn2, and Opa-1) and mitochondrial fission (Fis1, Drp1, and MTP18), which contribute to elevated proliferation of BMSCs.…”
Section: Mitochondrial Dynamics In Mscs Under Physical Stress and Toxinsmentioning
confidence: 97%
“…In vitro studies of the effects of very high doses (900 Gy) of X-rays to the lenses of guinea pigs, in 53 mmHg or 7% oxygen, found the oxygen consumption (by electrical conduction) was reduced by half in young guinea pigs but exhibited no change in lenses of adult animals (Hockwin and Bergeder 1958). Albeit, for normoxic conditions and non-ocular cells, high-LET irradiations augmented the mtDNA copy number (0.4 and 0.8 Gy), while low-LET enlarged the aggregated mitochondrial length (2 and 10 Gy) (Zhang et al 2013;Patten et al 2019). Moreover, high-LET a-particles increased mitochondrial mass and the transformation and oxygen consumption of human small airway epithelial cells but decreased the efficiency of mitochondrial respiration (Zhang et al 2013).…”
Section: Oxygen Tension Antioxidants and Metabolomicsmentioning
confidence: 98%
“…Moreover, high-LET a-particles increased mitochondrial mass and the transformation and oxygen consumption of human small airway epithelial cells but decreased the efficiency of mitochondrial respiration (Zhang et al 2013). However, four hours after low-LET X-rays, the mitochondria in mesenchymal stem cells produced more ATP by creating respiratory super-complexes and greater respiration in longer mitochondria, but eight hours post-irradiation, the cells reverted to normal oxygen consumption (Patten et al 2019).…”
Section: Oxygen Tension Antioxidants and Metabolomicsmentioning
confidence: 99%
“…Radiation therapy is a critical component of many cancer treatments and understanding how mitochondria are affected by radiation is crucial for optimizing treatment and subsequent quality of life for cancer patients. Ionizing radiation is known to alter mitochondrial function, increase mitochondrial oxidative stress, and induce apoptosis, which collectively would be beneficial for killing tumor cells but is unwanted in healthy tissues (75,76). Clinically, the main cause of radiotherapy failure is the development of cellular radioresistance, which can be conferred by various mechanisms including chances in glycolysis or mitochondrial metabolism (77); indeed, targeting those mechanisms has been shown to improve radiotherapy responses (3,78,79).…”
Section: Radiation Therapymentioning
confidence: 99%